2015
DOI: 10.3126/kumj.v13i1.13761
|View full text |Cite
|
Sign up to set email alerts
|

Point-of-care Ultrasonography in Critically Ill Patients

Abstract: Point-of-care ultrasonography has been used frequently by the physicians involved in managing critically ill patients. It allows direct visualization of pathology or abnormal physiological state at the bed side. The examination may be safely and effectively repeated as needed to follow the evolution of illness and the response to therapy. It is helpful to guide the therapy in patients with undifferentiated shock and for bedside diagnosis of common pathological conditions in acute care setting. It can facilitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…Measurement of ONSD is rapidly gaining popularity as it is quick, easily available and has a short learning curve. The optic nerve sheath is continuous with dura mater, and subarachnoid compartment of optic nerve communicates with that of brain so that any increase in ICP causes expansion of ONSD (9) .…”
Section: Discussionmentioning
confidence: 99%
“…Measurement of ONSD is rapidly gaining popularity as it is quick, easily available and has a short learning curve. The optic nerve sheath is continuous with dura mater, and subarachnoid compartment of optic nerve communicates with that of brain so that any increase in ICP causes expansion of ONSD (9) .…”
Section: Discussionmentioning
confidence: 99%
“…For pulmonary embolisms, LUS exams can show the pulmonary infarction area, defined as triangular or rounded, hypoechoic, homogeneous subpleural consolidation [39]. A meta-analysis by Squizzato et al [40] revealed an overall 87% sensitivity and 82% specificity for pulmonary embolism diagnoses using LUS examinations.…”
Section: Pulmonary Embolismmentioning
confidence: 99%
“…As the optic nerve sheath is continuous with dura mater, and subarachnoid compartment of optic nerve communicates with that of brain, any increase in ICP causes expansion of ONSD. [95][96] Measurement made 3 mm behind the globe is most optimal. 97 Inter-individual variation makes cut-off value hard to define and have ranged from 4.8-6.0mm with a sensitivity of 36-90% and specificity of 38-100%.…”
Section: Icp Monitoringmentioning
confidence: 99%